ANALISIS PENDAPATAN PEMBESARAN BEBEK PEDAGING DI DESA SUMBER JAYA KECAMATAN BELITANG II KABUPATEN OKU TIMUR - Muridin (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2018)
Muridin. 2017. To increase livestock development, the current development approach is through the development of livestock-based agribusiness areas. Currently in East OKU Regency there are a lot of food stalls (tent stalls) on the side of the road, the market sells food made from duck meat (fried duck), so it is necessary to provide duck meat ingredients that are raised by the community. Based on the description above, the researcher is interested in carrying out research on